2009
DOI: 10.1177/0020764008096853
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Comparison of Culturally Based Explanations for Mental Disorder Among Singaporean Chinese Youth

Abstract: While groups differed in their endorsement of supernatural explanations, psychological perspectives had the strongest endorsement among this population. Regression analysis showed that individuals who endorsed supernatural explanations more strongly tended to have no exposure to psychology courses and heightened religiosity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For example, alternative explanatory models for asthma have been described in other ethnic-racial groups [69] and in other diseases [7073]. Explanatory models are important to elicit for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…For example, alternative explanatory models for asthma have been described in other ethnic-racial groups [69] and in other diseases [7073]. Explanatory models are important to elicit for several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of Chinese youths in Singapore showed that some youths believed in the Asian physiological explanation of mental illness (eg, traditional Chinese beliefs of a body out of balance or harmony) or attributed mental illness to religious and supernatural influences. 19 These beliefs could be related to some youths’ preference for seeking help from Traditional Chinese Medicine physicians. 20 Although participants in these studies also showed beliefs in psychological causes of mental illness and preference for seeking help from mental health professionals, the findings suggest that one’s cultural background may influence one’s views of mental illness.…”
Section: Introductionmentioning
confidence: 99%